EFEKTIFITAS METODE TANGGUNG RENTENG DALAM MENGATASI KREDIT MACET DI BANK WAKAF MIKRO DENANYAR SUMBER BAROKAH JOMBANG - Azizah, Ninik; Islamiyah, Shohibatul (Irtifaq, 2021)
This study intends to analyze the effectiveness of the joint responsibility method at the Micro Waqf Bank Denanyar Sumber Barokah Jombang, analyze the effectiveness of the application of the joint responsibility method to the customers of the Micro Waqf Bank Denanyar Sumber Barokah Jombang. There are two sources of data in this study, namely primary data sources and secondary data. Finished collecting data, to analyze the author using descriptive method. Analysis of the data obtained from this study shows that the purpose of implementing this strategy is to form a customer character and teach the group an attitude of responsibility so that they are willing to pay installments on time (disciplined) and the Micro Waqf Bank Denanyar Sumber Barokah is able to reduce the number to avoid risk. customer default or bad credit. Keywords: Micro Waqf Bank. Joint Liability, Bad Credit.